Management of quality processes in times of global reconceptualization - León, Jesenia; Avellan Guaranda, Avellan Guaranda (Conexiones UG, 2024)
Understanding what management by quality processes means in times of global reconceptualizations involved, as a purpose or objective, making some differentiating conceptual considerations and practices in relation to management by results, the state models and the economic models that have governed quality systems. management. Said differentiation goes through characterizing the distinctive elements of the liberalist- neoliberalist economic model, such as forms or structures in which the functions of the welfare state are slimmed down to give way only to the private, reducing any possibility of social and collective development and with it forms of social economic undertakings that generate employment and productivity. In this sense, the characterizing elements of the process management model are outlined in the dissertation presented, supported by a state approach based on macroeconomic balances, in the search for socioeconomic enterprises that generate employment. In this way, the requirement of having previously identiﬁed the needs and concerns to undertake forms of knowledge planned and subjected to analysis that allow the location of real problems that impact a social world, beyond presenting results, product of improvisations, is concluded. immediacy, proceduralism and technicalities, which rather than promote signiﬁcant advances, new work proposals, inclusion processes and economic development, become a farce disguised as science.